Jack Mezirow Transformative Learning in Islam: A Case Study of Micro-Credential Perceptions and Students' Lifelong Learning - Guefara, Rahmat Lutfi; El Syam, Robingun Suyud; Suwadi, Muhammad Ardin (Universitas Wahid Hasyim Semarang, 2024)
AbstractThis research explores Jack Mezirow's transformative learning theory in the context of Islamic education. It focuses on the perception of micro-credentials and lifelong learning, aiming to provide a comprehensive understanding of these concepts in Islamic pedagogy. This type of research is field research using qualitative methods that focus on a case study approach to investigate how transformative learning can be implemented effectively in Islamic education and how micro-credentials influence perceptions of learning. Data collection techniques used interviews, observation and documentation with sampling using purposive techniques with 10 teachers and 50 students as respondents. These findings highlight that transformative learning fosters deeper religious understanding and behavioral change in students, while micro-credentials increase engagement by recognizing small educational achievements. This research offers insights into how lifelong learning and transformative approaches can improve the quality of Islamic education, supporting critical and reflective thinking among students. The impact of this research is to increase higher quality Islamic education learning with a multidisciplinary approach.